A systematic review and meta-analysis of the kynurenine pathway of tryptophan metabolism in rheumatic diseases - Mangoni, Arduino A.; Zinellu, Angelo (Frontiers in Immunology, 2023)
There is an increasing interest in the pathophysiological role of the kynurenine pathway of tryptophan metabolism in the regulation of immune function and inflammation. We sought to address the link between this pathway and the presence rheumatic diseases (RD) by conducting a systematic review and meta-analysis of studies reporting the plasma or serum concentrations of tryptophan, kynurenine, and other relevant metabolites in RD patients and healthy controls. We searched electronic databases for relevant articles published between inception and the 30 th of June 2023. Risk of bias and certainty of evidence were assessed using the Joanna Briggs Institute Critical Appraisal Checklist and the Grades of Recommendation, Assessment, Development and Evaluation Working Group system. In 24 studies selected for analysis, compared to controls, RD patients had significantly lower tryptophan (standard mean difference, SMD= -0.71, 95% CI -1.03 to -0.39, p˂0.001; I 2 =93.6%, p<0.001; low certainty of evidence), and higher kynurenine (SMD=0.69, 95% CI 0.35 to 1.02, p<0.001; I 2 =93.2%, p˂0.001; low certainty), kynurenine to tryptophan ratios (SMD=0.88, 95% CI 0.55 to 1.21, p˂0.001; I 2 =92.9%, p˂0.001; moderate certainty), 3-hydroxykynurenine (SMD=0.74, 95% CI 0.30 to 1.18, p=0.001; I 2 =87.7%, p˂0.001; extremely low certainty), and quinolinic acid concentrations (SMD=0.71, 95% CI 0.31 to 1.11, p˂0.001; I 2 =88.1%, p˂0.001; extremely low certainty). By contrast, there were non-significant between-group differences in kynurenic acid, 3-hydroxyanthranilic acid, kynurenic acid to kynurenine ratio, or quinolinic acid to kynurenine acid ratio. In meta-regression, the SMD of tryptophan, kynurenine, and kynurenine to tryptophan ratio were not associated with age, publication year, sample size, RD duration, C-reactive protein, or use of anti-rheumatic drugs and corticosteroids. In subgroup analysis, the SMD of tryptophan, kynurenine, and kynurenine to tryptophan ratio was significant across different types of RD, barring rheumatoid arthritis. Therefore, we have observed significant alterations in tryptophan, kynurenine, 3-hydroxykynurenine, and quinolinic acid concentrations in RD patients. Further research is warranted to determine whether these biomarkers can be useful for diagnosis and management in this patient group. (PROSPERO registration number: CRD CRD42023443718).